Heterogeneous ices in ice wedges structure on the Pur-Taz interfluve peatlands of the north of West Siberia - Ya. V. Tikhonravova; E. A. Slagoda; V. V. Rogov; V. I. Butakov; A. V. Lupachev; A. O. Kuznetsova; G. V. Simonova (Лëд и снег, 2020)
Structure of arctic peatlands with massive ice and structure-forming ice were studied in drained lake («khasyrey») of the Pur-Taz interfluves (the north of West Siberia). The period of accumulation of two-meter thickness of the peat was established to be changed from 8413±90 to 897±90 years BP. Composition of the peat deposits is represented by Betula nana, Sphagnum  sp., Vaccinium oxycoccos, Eriophorum  sp., Equisetum sp. The massive ice is represented by ice wedges with large shoulders and young ice wedges. The central part of the ice wedge is composed by recrystallized crystals of ice veins. Melting zones (elongated crystals of segregated ice and closed-cavity ice) were found in the shoulders of the ice wedge and in the upper part of the young ice wedge. Young ice wedges in the central and lateral parts the main wedge have a similar structure in the cross-section, but they are built by different genetic types of ice: the ice veins or closed-cavity ice with segregated ice. Ice-rich peat contains different types of ice inclusions and subhorizontal ice belts and ice lenses. Ice lenses in the peat can be formed by the segregated ice and/or infiltrated-segregated ice. The hydrochemical composition of the ice wedges, ice lenses, surface water samples and the aqueous extract from peat was analyzed. Hydrochemical analysis did show that polygonal-core ice has basically similar composition with the present-day atmospheric precipitation and surface waters of the polygonal bath; in the area of the shoulder – the composition is intermediate between the ground waters of peat and the central part of the vein. The hydrochemical composition of the ice lenses is similar to the composition of the lake water and peat underlying the active layer. The methane concentrations and its distribution within the ice wedges, peat and lens ice were determined. The closed-cavity ice doesn’t contain methane; the ice wedges with ice veins have minimal methane concentrations; large ice lenses have differentiation of methane concentrations. High concentrations of methane are typical for the frozen peat with inclusions of closed-cavity ice in the uppermost part of permafrost layer; the maximum methane concentration was determined inside the peat with ice lenses. The heterogeneous ices inside the ice wedges, distribution of hydrochemical compounds and methane distribution were conditioned by dynamics of the melting depth during the peatland formation under changing climate of the Holocene in the Arctic.